Derivados dos ácidos clorogênico, cafeico e cinâmico: obtenção, avaliação da atividade antimicrobiana e de inibição enzimática - Adolpho, Luciana de Oliveira (2012)
In recent years there has been an increase in researches for new enzyme inhibitors on medicinal plants used in the treatment of disorders such as schizophrenia, anxiety, amnesia, different stages of depression and bipolar affective disorder. The study of enzymatic inhibitors of prolyl oligopepetidase (POP) and acetylcholinesterase (AChE) are directly related to the treatment of central nervous sistem diseases. In a research with the species Hypericum brasiliense, native from Brazil, it was isolated as main secondary metabolite the chlorogenic acid, a compound able to inhibit POP and AChE. From this observation, three series of chlorogenic, caffeic and cinnamic acids derivatives were obtained through simple derivatization reactions and coupling with the amino acid proline. The derivatives were obtained by usual acetylation, methylation and esterification reactions with satisfactory yields of 50-90%. The couplings with the proline methyl ester were performed using either O-(7- azabenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU)/ diisopropylethylamine (DIEA) in dimethylformamide or isobutyl chloroformate/ Nmethylmorpholine in tetrahydrofuran. The derivatives were tested against the enzymes POP, AChE and dipeptidyl oligopeptidase (DPP IV). Also, a study was conducted to determine the antibacterial and antifungal activities of all derivatives. The capacity of the tested compounds to inhibit DPP IV and AChE was not exceptional. In contrast, the derivatives methyl ester and 1,7-acetonide obtained from chlorogenic acid, and caffeic acid and its methyl ester derivative showed selectivity and satisfactory performance as POP inhibitors, with IC50 values of 3 to 14 μM. All compounds showed moderate antimicrobial activity.